MUI Fatwa on the Prohibition of Interfaith Greetings: Analysis of the Perspective of Postmodernist Social Theory in the Context of Plural Society - Moch. Ikwan Ikwan; Abd. 'A'la; Mohamad Salik; Mufaizah (Journal of Islamic Civilization, 2024)
This research is based on the fatwa of the Indonesian Ulema Council (MUI) on the prohibition of interfaith greetings, which has sparked widespread debate in Indonesia's pluralistic society, which has given rise to tensions between Islamic theological values and the demands of social diversity in the context of religious pluralism. This research aims to analyze the fatwa from the perspective of postmodern social theory. The scope of the study covers the theological, sociological, and social implications of the fatwa's implementation in society. The method used is a qualitative study with a document analysis approach and a literature review of the official MUI statement, public responses, and postmodern social theories. The results of the study indicate that the MUI fatwa is based on efforts to maintain the purity of the Islamic faith, but in the context of a pluralistic society it can give rise to social exclusivism and resistance to the values of inclusivity. In conclusion, although this fatwa has a strong normative basis from a religious perspective, its implementation requires a more adaptive socio-cultural approach to avoid polarization amidst the diversity of Indonesian society.